Anatomorradiographic description of the capybara´s teeth (Hydrochoerus hydrochaeris) - Tiai Kihara, Mariana [UNESP]; Salvitti de Sá Rocha, Thiago André [UNESP]; Carmo Santos, Caio Cesar [UNESP]; Senna Fechis, Alisson Diego [UNESP]; Aparecida Alves, Ana Carolina [UNESP]; de Castro Sasahara, Tais Harumi [UNESP]; de Oliveira, Fabrício Singaretti [UNESP] (Universidade Federal do Rio Grande do Sul, 2019)
Background: The capybara (Hydrochoerus hydrochaeris) is the largest South American rodent species alive, and it preferentially inhabits floodable environments. Currently, capybara populations have been increasing owing to lack of predators and increased availability of food. This favors reemergence of Rocky Mountain spotted fever in the state of São Paulo, as these animals can play host to the Cayenne tick (Amblyomma cajennense), a vector of the bacteria that transmit this disease. The objective of this work was to perform anatomical and radiographic analyses on the teeth of capybaras to broaden knowledge on the morphology of this species, as scientific interest on capybaras has been growing owing to reemergence of Rocky Mountain spotted fever. Materials, Methods & Results: Six capybara carcasses from the state of São Paulo, Brazil, were taken to the Laboratory for Animal Anatomy of the School of Agricultural Sciences and Veterinary Medicine of UNESP - Jaboticabal for obtainment of heads by disarticulation of the cervical region. The heads were frozen at -18°C, and then sectioned medially with a band saw to avoid tissue overlap in radiographs. The head halves were radiographed in the Diagnostic Imaging Section at the Veterinary Hospital of UNESP-Jaboticabal in laterolateral projection. After taking the radiographs, the teeth were extracted from the dental arches using anatomical forceps and pliers, placed in 0.1% thymol, and kept at 4°C for up to 30 days. The teeth were dried using an air jet produced by a compressor, and placed in molds made of aluminum foil. The specimens were embedded in alternating layers of clear polymethylmethacrylate and liquid polymerization catalyst until each tooth was completely covered. After 24 h, the molds were removed, and the blocks were sectioned using a band saw. Transversal and longitudinal calcified tooth sections with a thickness of 1.5 mm were prepared. The sections were sanded using an automotive sander with 80-grit sandpaper, and then sanded by hand until a thickness of 0.12 mm was reached. The tooth fragments were removed from the resin, dehydrated in ethanol, clarified in xylene, and placed in a Petri dish containing glycerin for evaluation using a mesoscope and a negatoscope. Capybaras were found to have one incisor, one premolar, and three molar teeth in each dental hemiarch (superior and inferior). All teeth contained large, open roots. The root of the superior incisor is rostral to the root of the premolar tooth, and the root of the inferior incisor lies between the roots of the premolar and the first molar teeth. The inferior incisors are much larger than their superior counterparts, and their ends are chisel-shaped. The pulp cavity extends from the apical region to up to two-thirds of the longitudinal length of the tooth, and the enamel is arranged in layers. The roots of the four molar teeth are large and resemble several aggregated laminae arranged longitudinally - five laminae in the inferior molars, four laminae in the premolar, first and second molars, and 13 or 14 laminae in the third superior molar. Discussion: The dental formula of capybaras is similar to that of guinea pigs, chinchillas, and pacas, but different from that of agoutis. All teeth are aradicular as in guinea pigs and chinchillas because of the great tooth wear owing to feeding. In chinchillas and guinea pigs, the apex of the mandibular incisor tooth is located between the second and the third molar; in capybaras, it is located between the premolar and the first molar. The premolar and molar teeth of capybaras are similar to their counterparts in the paca and to the molars of elephants because they exhibit parallel internal laminae. The teeth of capybaras are similar to those of guinea pigs in terms of number and type of teeth, and similar to those of pacas and elephants regarding external morphology.
Descrição anatomorradiográfica dos dentes da capivara (Hydrochoerus hydrochaeris)
Keywords: Anatomy; Dentition; Rodent; Wild animal; X-ray